A SUCCESSION PLAN IS NEEDED FOR OPERATING ROOM NURSES - Desrosiers, Gyslaine (Operating Room Nurses Association of Canada Journal, 2008)
Nothing appeals to people’s imaginations quite as much as the mysterious goings-on in an operating room –that place where consciousness fades, where the heart stops beating, where blood is shunted through a pump as bones are sawed and nailed back together and the brain is laid bare. Where the soul waits to flow back into a damaged body filled with new hope.